If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -3(y + -6) + 2 = 6 Reorder the terms: 4y + -3(-6 + y) + 2 = 6 4y + (-6 * -3 + y * -3) + 2 = 6 4y + (18 + -3y) + 2 = 6 Reorder the terms: 18 + 2 + 4y + -3y = 6 Combine like terms: 18 + 2 = 20 20 + 4y + -3y = 6 Combine like terms: 4y + -3y = 1y 20 + 1y = 6 Solving 20 + 1y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 1y = 6 + -20 Combine like terms: 20 + -20 = 0 0 + 1y = 6 + -20 1y = 6 + -20 Combine like terms: 6 + -20 = -14 1y = -14 Divide each side by '1'. y = -14 Simplifying y = -14
| 12^(3/5)= | | 3000-15x=3500-25x | | 3500-25x=3000-15x | | D(ln8x)/Dx= | | 2.3=2X+X | | Y-58=-43 | | x+y+x=30 | | 86*5*2=x | | 86*5*2= | | (x*5)*2=1444 | | 22x=18x+12 | | -2=v+3 | | 12+18x=22x | | x+x+(x-24)=90 | | xsquared-4x-45=0 | | 3500+35x=3100+45x | | 5x+6x=3x+24 | | x^4+-5*x^3+5*x^2-6=0 | | 2m+5n+8m+4n= | | 3x+2y+z=21 | | x^2+3kx-k=1 | | 3x+2y+z=22 | | 20n^2-180=0 | | (y-k)(y-k)= | | (x^2)+2x=0 | | 5(4x-7)-2(3x+4)+10=3(3x-5)-43 | | 3x-(x+5)= | | 8x+12y=15 | | x^2-(a+b)x-ab= | | 6x^2-48x+96=300 | | 160,000/1/3 | | 6x^2-396=0 |